Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1210/jc.2012-2340
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Strength in Young Asian Indian Females after Vitamin D and Calcium Supplementation: A Double-Blind Randomized Controlled Clinical Trial

Abstract: Oral cholecalciferol/calcium supplementation in the dose/schedule used is effective and safe in increasing and maintaining serum 25(OH)D. However, this does not lead to improved skeletal muscle strength in young females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 23 publications
4
61
3
Order By: Relevance
“…Difference in vitamin D levels in both sexes were statistically significant (p value=0.0025). Similar results were found in study done by Asghai et al, Goswami et al, Johnson et al, Merlino et al [6][7][8][9] Prevalence of vitamin D deficiency was more in urban population in comparison to rural population in this study. 16% urban and 40% of rural population were having normal vitamin D levels.…”
Section: Discussionsupporting
confidence: 92%
“…Difference in vitamin D levels in both sexes were statistically significant (p value=0.0025). Similar results were found in study done by Asghai et al, Goswami et al, Johnson et al, Merlino et al [6][7][8][9] Prevalence of vitamin D deficiency was more in urban population in comparison to rural population in this study. 16% urban and 40% of rural population were having normal vitamin D levels.…”
Section: Discussionsupporting
confidence: 92%
“…4 Khadgawat et al, Garg et al and various other studies have also reported a high prevalence of vitamin D deficiency in Indian population. [6][7][8][9][10][11][12][13] In the present study, we found that after supplementation with vitamin D, the weight SD score of children increased significantly. This is due to direct influence of vitamin D levels on weight of the children.…”
Section: Discussionmentioning
confidence: 75%
“…The effect of vitamin D supplementation on muscle strength in females was not observed [34]. Further investigation of their earlier study found that the improvement in hand grip strength was only in males, suggesting a possible gender-specific difference [34]. With lower doses of vitamin D supplementation (400 IU/day and 1000 IU/day), no significant improvement in muscle strength was seen among immigrants with ethnic backgrounds of Middle Eastern, African and South Asian in Oslo (aged 18-50 years) [1].…”
Section: Factors Affecting Vitamin D Statusmentioning
confidence: 90%
“…To distinguish whether the positive effect on muscle strength was due to calcium, vitamin D or the combination of both, the same research group conducted a different RCT study, but this time only among young females. The effect of vitamin D supplementation on muscle strength in females was not observed [34]. Further investigation of their earlier study found that the improvement in hand grip strength was only in males, suggesting a possible gender-specific difference [34].…”
Section: Factors Affecting Vitamin D Statusmentioning
confidence: 95%